2016
DOI: 10.3389/fmicb.2016.01625
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Protoheme IX Farnesyltransferase CtaB Causes Virulence Attenuation but Enhances Pigment Production and Persister Survival in MRSA

Abstract: The membrane protein CtaB in S. aureus is a protoheme IX farnesyltransferase involved in the synthesis of the heme containing terminal oxidases of bacterial respiratory chain. In this study, to assess the role of CtaB in S. aureus virulence, pigment production, and persister formation, we constructed a ctaB mutant in the methicillin-resistant Staphylococcus aureus (MRSA) strain USA500. We found that deletion of ctaB attenuated growth and virulence in mice but enhanced pigment production and formation of quinol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 63 publications
0
27
0
Order By: Relevance
“…Typically, clinical SCVs and ΔhemB mutants show no or decreased pigment production compared to that of the wild type (20). However, when CtaB, the enzyme that catalyzes the very last step of the pathway and couples the farnesyl diphosphate chain to protoheme IX, is removed in S. aureus, an increased pigmentation is observed, indicating that farnesyl diphosphate is fed into the pigment production pathway (30). Since the insertion into hemY interrupts the pathway between the steps catalyzed by HemB and CtaB, the hemY mutant was supplemented with hemin on an agar plate to assess staphyloxanthin production in the absence and presence of hemin.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, clinical SCVs and ΔhemB mutants show no or decreased pigment production compared to that of the wild type (20). However, when CtaB, the enzyme that catalyzes the very last step of the pathway and couples the farnesyl diphosphate chain to protoheme IX, is removed in S. aureus, an increased pigmentation is observed, indicating that farnesyl diphosphate is fed into the pigment production pathway (30). Since the insertion into hemY interrupts the pathway between the steps catalyzed by HemB and CtaB, the hemY mutant was supplemented with hemin on an agar plate to assess staphyloxanthin production in the absence and presence of hemin.…”
Section: Resultsmentioning
confidence: 99%
“…After terminal repair, base A and sequencing connector were added, the target fragments were collected by agarose gel electrophoresis, and amplified by PCR. The whole library was prepared and the library was sequenced by Illumina HiSeq2500 [21].…”
Section: Rna Isolation Mrna Enrichment and Sequencingmentioning
confidence: 99%
“…Stationary phase S. aureus persister formation is associated with low membrane potential (39), while phenol-soluble modulins limit S. aureus prsister cell formation (40). Deletion of ctaB can attenuate S. aureus growth and virulence in mice but enhanced the formation of persister cells in stationary phase (41).…”
Section: Introductionmentioning
confidence: 99%
“…It has been hypothesized that persister genes may overlap with virulence genes (28, 48). Few studies explored the relationship between virulence and persister formation, and mostly it remains unclear (41). In the present study, we identified by mutant library screen a new transcription factor NWMN_0037 which we named RpvA based on its involvement in both persister formation and virulence in S. aureus .…”
Section: Introductionmentioning
confidence: 99%